(untitled) (Sustainability in Debate, 2022)
Russian military invasion of Ukraine became yet another reminder to humanity about how fragile our world is and how it requires unity and partnership to confront global humanitarian challenges and to ensure goals of sustainable development. The article analyzes the historical context of the establishment of Ukrainian statehood, provides situational assessment of the current state of economy and environmental hazards in Ukraine and investigates successful anti-crisis «success stories» of other countries. It is namely on this basis that a strategy of changing an existing system of state governance in Ukraine has been elaborated, taking into account the consequences of the war-induced socio-economic crisis. As conceptual framework for this strategy, provisions of the sustainable development theory were utilized, regarded by the authors as the most implementable «survival guide» for contemporary world.